N. Kh. Bunhe (1823-1895) – a financier, economist and statesman of the Russian empire - Todoriuk, O. B. (History of science and technology, 2013)
The life and activity of the prominent Russian financier, economist and statesman, who played a particular role in the development of Russian empire as a state have been highlighted in the article